Sociological Analysis of Transition as a Contribution to Study of social changes - Nedeljković, Marina D (Sociološki pregled, 2018)
Uroš Šuvaković: Transition, Contribution to Sociological Study of Social Changes. Kosovska Mitrovica: University of Priština, Faculty of Philosophy,2014, 368 pp